Excavations at ziyaret tepe, diyarbakir province, Turkey, 2011-2014 seasons - (:unkn) unknown (Nederlands Instituut voor het Nabije Oosten, 2015)
This article presents the results of excavations at Ziyaret Tepe, the Late Assyrian city of Tušhan in the Diyarbakir Province of southeastern Turkey during the summers of 2011-2013, as well as from a study season in 2014. Excavation in nine operations is briefly summarized, and the preliminary results of zooarchaeological and archaeobotanical studies in three operations are presented. Major public buildings of the Late Assyrian period (c. 882- 611 BC) were recovered in Operation AN (palace), Operation W (administrative building), and Operation Y (city fortification), while an exposure of domestic architecture was revealed in Operation K Also of importance from these field seasons was the documentation of a Late Roman, or Late Antique, occupation in Operations T and U. Zooarchaeological evidence from earlier excavations in Operation K reveal the subsistence practices of commoners during the Late Assyrian period. Likewise, the use of plants for human food and animal fodder are discussed for the Late Assyrian (Operation Q, the city gate excavated earlier) and the Late Antique (Operation T, domestic housing) periods. These combined reports outline the importance of animal husbandry, as well as agricultural production of grain, as key economic aspects of the Late Assyrian settlement, and complement existing cuneiform documentation.